2D-nanomaterials for controlling friction and wear at interfaces. Issue 3 (June 2015) - Spear, Jessica C.; Ewers, Bradley W.; Batteas, James D.
Graphical abstract: Highlights: Compilation of computed interlayer sliding interaction parameters. Nanoscale and macroscale tribological studies on 2D nanomaterials. Single atomic layered lubricants. 2D nanomaterials as lubricant additives. Abstract: This review focuses on recent developments in the use of 2D nanomaterials for controlling the frictional properties of surfaces and interfaces. While materials such as MoS2 and graphite have been investigated for some time, a host of other layered nanomaterials have emerged as alternatives for friction modification. These advanced lubrication schemes provide an opportunity to address growing needs in energy and materials efficiency and device compatibility, offering improved boundary and solid lubrication of contacting and sliding interfaces. Here, we describe both computational and experimental investigations of the mechanisms and implementations of 2D nanomaterials in the lubrication of interfaces.